Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1055/s-0028-1095157
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro-Untersuchungen über den Fettstoffwechsel isolierter menschlicher Fettzellen in Abhängigkeit von der Zellgröße: Die durch Adrenalin induzierte Lipolyse.

Abstract: An isolierten menschlichen Fettzellen wurde die Beziehung zwischen lipolytischer Aktivität und der Fettzellgröße untersucht. Dazu wurden bei 16 chirurgischen Patienten mit unterschiedlich ausgeprägtem Unter-bzw. Übergewicht intra operationem subkutanes Fettgewebe aus dem Abdominalbereich entnommen und mittels Kollagenase die Fettzellen isoliert. Die spontane und durch Adrenalin induzierte Lipolyse wurde nach einstündiger Inkubation der Fettzellen in albuminhaitigern Krebs-Ringer•Bikarbonat-Puffer gemessen. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

1970
1970
1988
1988

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…4. Correlation between relative body weight and adipocyte volume in maturity onset-diabetics cedure leads to values which were never exceeded by our measurements, and, as far as can be seen, in the literature [7,8,13,14]. There are several reasons for the statement of a maximum adipocyte size, e.g.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…4. Correlation between relative body weight and adipocyte volume in maturity onset-diabetics cedure leads to values which were never exceeded by our measurements, and, as far as can be seen, in the literature [7,8,13,14]. There are several reasons for the statement of a maximum adipocyte size, e.g.…”
Section: Discussionsupporting
confidence: 73%
“…In the other extreme, Martinsson [17] only found the adipocyte number, but not the adipoeyte size, correlated with the weight index. A distinction between hypertrophy and hyperplasia of the adipose tissue is of great practical importance, since there exists a positive correlation between adipocyte volume and basal lipolysis [8,13,18]. Elevated serum concentrations of free fatty acids in obesity cause a metabolic situation which promotes the manifestation of maturity onset-diabetes [19--21].…”
mentioning
confidence: 99%
“…Calculations. The average lipid content of the single fat cell was calculated according to Faulhaber [4], using the follo~ng formula From the lipid content of the single fat cell and the EFA content of the tissue, the cell number was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma glycerol and FFA concentration were not changed by physical training. It has previously been shown that there is a correlation between cell size and lipolysis in uitro (Faulhaber et al 1969, Smith 1970, Goldrick and McLoughlin 1970, Bjorntorp and Sjostrom 1972. The fact that the glycerol and FFA levels were not changed in spite of the reduced adipose mass because of smaller fat cells may indicate enhanced lipolysis in these smaller fat cells as suggested by other authors (Froberg et al 1972, Askew et al 1973.…”
Section: Discussionmentioning
confidence: 63%